2010
DOI: 10.1177/0002764210381712
|View full text |Cite
|
Sign up to set email alerts
|

Words and Their Ways in Campaign ’08

Abstract: This study reports certain lexical patterns produced during the general election of campaign 2008 by Senators

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 19 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Previous work found nominees increased their use of campaign themes moving into the general (Coe and Reitzes 2010), but Biden did not do so. Hart and Lind (2010) found that Obama and McCain increased their use of language describing immediate issues that affect people's everyday lives as they moved into the general election. Perhaps Biden focused his rhetoric on addressing the acute and dire reality of a growing pandemic versus emphasizing more abstract messages about restoring the soul of the nation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work found nominees increased their use of campaign themes moving into the general (Coe and Reitzes 2010), but Biden did not do so. Hart and Lind (2010) found that Obama and McCain increased their use of language describing immediate issues that affect people's everyday lives as they moved into the general election. Perhaps Biden focused his rhetoric on addressing the acute and dire reality of a growing pandemic versus emphasizing more abstract messages about restoring the soul of the nation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the relevance of Twitter in modern campaigning, it is important to assess how running mates use this platform. Second, while there is some research charting how eventual nominees communicated in the primaries and general election (e.g., Acree et al 2020; Coe and Reitzes 2010; Hart and Lind 2010), there is no work systematically tracking the evolution of how two separate campaigns rhetorically become one. This study provides such analysis and in doing so it illuminates how they each evolved their communication, as well as the potential interactive effects on each other's campaign communications, such as how running mates realign communicatively to suit the nominee.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, if one were to write an opinion piece about radiology residency training, the tone of this piece might differ considerably if it is written in a time of plentiful employment, favorable payment structures, and technologic innovation as opposed to a time of job scarcity, stagnant development, and large-scale turf wars with other specialties. The words an author or speaker chooses to express opinion have been shown to accurately reflect this ambience (2,3).…”
Section: Special Report: Reading the Writing In Radiologymentioning
confidence: 99%
“…Not only has computerized content analysis been used in the field of finance, but it has also been employed in the context of political science to assess the rhetorical styles and affect of political communications (see for instance Forsythe, 2004;Hart and Childers, 2004;Hart and Lind, 2010;Davis and Gardner, 2012;Young and Soroka, 2012). However, to the best of our knowledge, the existing literature has largely overlooked the question of how the sentiment and other characteristics of communications issued by political leaders influence stock market valuations.…”
mentioning
confidence: 99%